2016
DOI: 10.3945/ajcn.115.123216
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of dairy foods and diabetes incidence: a dose-response meta-analysis of observational studies

Abstract: Background: A growing number of cohort studies suggest a potential role of dairy consumption in type 2 diabetes (T2D) prevention. The strength of this association and the amount of dairy needed is not clear. Objective: We performed a meta-analysis to quantify the associations of incident T2D with dairy foods at different levels of intake. Design: A systematic literature search of the PubMed, Scopus, and Embase databases (from inception to 14 April 2015) was supplemented by hand searches of reference lists and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
298
6
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(354 citation statements)
references
References 54 publications
(96 reference statements)
24
298
6
10
Order By: Relevance
“…The meta-analysis of fourteen cohort studies by Chen et al (48) also showed that yoghurt was associated with reduced risk of T2DM (RR 0·82, 95 % CI 0·70, 0·96 per one serving/d) whereas other dairy foods and consumption of total dairy products were not appreciably associated. The very recent meta-analysis of Gijsbers et al (49) involved twenty-two prospective studies with a total of 579 832 subjects including 43 118 T2DM cases. Total dairy products and low-fat dairy products were both inversely associated with T2DM risk (RR 0·97 per 200 g/d; 95 % CI 0·95, 1·00; RR 0·96 per 200 g/d; 95 % CI 0·92, 1·00, respectively).…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…The meta-analysis of fourteen cohort studies by Chen et al (48) also showed that yoghurt was associated with reduced risk of T2DM (RR 0·82, 95 % CI 0·70, 0·96 per one serving/d) whereas other dairy foods and consumption of total dairy products were not appreciably associated. The very recent meta-analysis of Gijsbers et al (49) involved twenty-two prospective studies with a total of 579 832 subjects including 43 118 T2DM cases. Total dairy products and low-fat dairy products were both inversely associated with T2DM risk (RR 0·97 per 200 g/d; 95 % CI 0·95, 1·00; RR 0·96 per 200 g/d; 95 % CI 0·92, 1·00, respectively).…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…Actualmente, la grasa láctea está cambiando el paradigma habitual de los ácidos grasos saturados (AGS) y los posibles daños sobre la salud con los que se relacionaba a los mismos. Las últimas evidencias publicadas demuestran que la grasa láctea, en comparación a otras grasas de origen animal, podría asociarse a posibles beneficios sobre la prevención de la diabetes mellitus tipo 2 (DM2) (12,13), el síndrome metabólico (SM) (14) y una menor ganancia de peso corporal (15), entre otros factores de riesgo cardiovascular. Además de AGS, el yogur contiene ácidos grasos trans (AGT) de origen natural.…”
Section: Lípidosunclassified
“…Los lácteos como el yogur contienen múltiples micronutrientes, incluyendo diversos minerales y vitaminas como Ca, sodio (Na), fós-foro (P), magnesio (Mg), zinc (Zn), iodo (I), potasio (K), vitamina A, vitamina D, vitaminas del complejo B, principalmente B 2 , B 3 y B 12 .…”
Section: Vitaminas Y Mineralesunclassified
“…Fire metaanalyser fant at spesifikt magre meieriprodukter var forbundet med lavere risiko for diabetes type 2 [184][185][186]188 . Chen og medarbeidere skilte ikke mellom magre og fete meieriprodukter i sin metaanalyse, men fant ingen sammenheng mellom meieriprodukter generelt og diabetes type 2 187 .…”
Section: Negativ Sammenhengunclassified
“…En nyere metaanalyse av Gijsbers og medarbeidere, som inkluderte 22 studier publisert til og med april 2015, fant imidlertid ikke en signifikant sammenheng mellom ost og diabetes type 2. 188 Gijsbers og medarbeidere fant en 5 prosent høyere risiko per 10 gram ost per dag blant menn, men dette var basert på kun to studier.…”
Section: Ingen Signifikant Sammenhengunclassified